2016
DOI: 10.1002/fee.1296
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing land use for the delivery of catchment ecosystem services

Abstract: Despite widespread implementation of best management practices, sustainable farming is neither practical nor possible in certain locations, where protecting water quality and promoting agricultural production are likely to be incompatible. Some strategic prioritization of land-use options and acceptance of continually degraded waterbodies may be required to ensure optimization of multiple ecosystem services in catchments (also known as watersheds or drainage basins). We examine approaches to prioritization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 50 publications
(97 reference statements)
0
52
0
Order By: Relevance
“…2a, b), pointing toward a differentiated stressor–response relationship between TP, SRP, and river ecology in different catchment types. This may be related to a number of complex interactions and “catchment resilience” factors such as river morphology, aquatic habitat structure, and riparian shading, as well as different bioavailability of P fractions, pointing toward a need for different prioritization of management interventions in catchments with different characteristics (Doody et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…2a, b), pointing toward a differentiated stressor–response relationship between TP, SRP, and river ecology in different catchment types. This may be related to a number of complex interactions and “catchment resilience” factors such as river morphology, aquatic habitat structure, and riparian shading, as well as different bioavailability of P fractions, pointing toward a need for different prioritization of management interventions in catchments with different characteristics (Doody et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…First, the export regimes observed exhibit large temporal and spatial variability in C, N and P dynamics: (i) the opposite seasonal dynamics of NO − 3 and SRP concentrations can lead to a switch from P limitation to N-P co-limitation during the summer growing season and (ii) transfer from different landscape units vary in space and time. This knowledge of temporal and spatial variability is necessary for prioritizing management efforts towards N or P according to a water quality target (for which the N : P ratio should be considered) and towards the landscape units most responsible for not attaining the water quality targets (Doody et al, 2016). Second, a comparison of seasonal export regimes in headwater and downstream reaches showed that attributing the seasonal SRP maximum during low flow only to point-source contributions could lead to ineffective management decisions if the wrong source is targeted.…”
Section: Implications For Monitoring and Managementmentioning
confidence: 99%
“…Service values beyond ecologically or socially accepted thresholds are not beneficial to management in a way that produces win-win outcomes (Qiu and Turner 2013). To meet health and environmental standards, more effort to reduce nitrogen loads from the watershed by reducing fertilizer inputs as well as maintenance and restoration of wetlands and abandoned rice fields may be required (Doody et al 2016). The fact that the nitrate concentrations (mean: 8.4 mg NO 3 /L, range: 0.07-44.0 mg NO 3 /L) in the 49 sub-watersheds averaged over five sampling times was lower than the water quality standards for drinking water (10 mg N/L [44.3 mg NO 3 /L]) suggests that the trade-off between crop production and water quality might be ameliorated in some subwatersheds.…”
Section: Management Implicationsmentioning
confidence: 99%
“…However, because nitrogen can be permanently removed from surface water via denitrification (Jordan et al 2003, Craig et al 2008, Roley et al 2012, much recent attention has focused on the question of whether watershed management may reduce downstream nitrate export without loss of agricultural function (Craig et al 2008). Some studies have suggested the possibility of ameliorating the trade-off between crop production and water quality by enhancing buffering capacity, including maintenance and restoration of wetlands, which remove nitrate effectively (Zedler 2003, Qiu and Turner 2015, Doody et al 2016, Hansen et al 2018.…”
mentioning
confidence: 99%